Physical Factors in Age-Related Decline Physical Performance among the Older Adults in Bandung - Vitriana Vitriana; Irma Ruslina Defi (Faculty of Medicine, Universitas Padjadjaran, 2020)
The aging process is associated with increased body fat and decreased muscle mass and strength in older adults. This condition is frequently associated with loss of mobility and functions. This study aimed to explore the relationship between physical performance and handgrip strength, body composition, and anthropometry in community-dwelling older adults living in Bandung, West Java Province, Indonesia. A cross-sectional study was performed from December 2015 to June 2016 on community-dwelling older adults above 60 years old who were the members of the West Java Branch of Lembaga Lansia Indonesia, Indonesia, with the ability to walk without an assistive device and to perform hand grip properly as an additional inclusion criterion. Subjects were excluded if they experienced severe cardiorespiratory or vascular abnormalities, used artificial implants, underwent hormone therapy, and had any disease that would affect the accuracy of the variable measurement. A total of 106 subjects (60-85 years old) participated in this study. A significant negative correlation between total body fat and physical performance and a positive correlation between handgrip strength to physical performance were observed among subjects. However, no correlation was found between the anthropometric measurement and physical performance. The total body fat percentage, muscle mass index, and handgrip strength correlate significantly to the physical performance in older adults and may be used as a good indicator to preserve physical function and quality of life in the elderly.Faktor-Faktor Fisik yang Memengaruhi Penurunan Performa Fisik Lanjut Usia di Lembaga Lansia Indonesia Cabang Jawa BaratProses penuaan sering dihubungkan dengan peningkatan lemak tubuh yang disertai dengan berkurangnya massa dan kekuatan otot pada lanjut usia. Kondisi ini sering berkaitan dengan hilangnya kemampuan mobilisasi dan fungsi lainnya. Tujuan penelitian ini adalah melihat hubungan antara performa fisik dengan kekuatan genggam tangan, komposisi tubuh dan antropometri pada komunitas lanjut usia yang tinggal di Bandung, Jawa Barat, Indonesia. Penelitian potong lintang dilakukan periode Desember 2015 sampai dengan Juni 2016 pada lanjut usia yang tinggal dalam komunitas dan merupakan anggota Lembaga Lansia Indonesia Cabang Jawa Barat, berusia lebih dari 60 tahun, serta mampu berjalan tanpa alat bantu dan dapat menggenggam tangan dengan baik. Partisipan dieksklusi bila menderita gangguan kardiorespirasi atau vaskuler yang berat, menggunakan implan artifisial, menjalani terapi hormonal dan mempunyai penyakit yang berpotensi mempengaruhi akurasi penilaian variabel. Dari total 106 partisipan dengan rentang usia 60–85 tahun, ditemukan korelasi negatif antara total lemak tubuh dengan performa fisik, dan korelasi positif antara kekuatan genggam tangan dengan performa fisik, akan tetapi tidak ditemukan hubungan antara komponen antropometri dengan performa fisik. Persentasi total lemak tubuh, indeks massa otot dan kekuatan tangan mempunyai hubungan yang bermakna dengan performa fisik pada lanjut usia dan dapat menjadi indikator yang baik dalam mempertahankan fungsi fisik dan kualitas hidup pada lanjut usia.